Surveying recent econometric forecasting performance - Spicey, W. Allen; Wrobleski, W.J. (Washington D.C. : American Enterprise Institute, 1979)
The series is intended to provide wider circulation within policy making and academic circles for selected papers and speeches by scholars and others associated with the institute
osc 15/01/2019
Loans
Keywords: Ecoometrics; Economic forecasting